Molecular polymorphism of the ABO system in Moroccan blood donors suggesting an A2 allele depression by B allele. (23rd November 2016) - Zarati, F.; Achtak, H.; Talbi, J.; Tissent, A.; Mifdal, H.; Khajij, T.; Nourichafi, N.; Bouisk, K.; Habti, N.
Abstract : Background: Several previous studies have determined the phenotypic and genetic frequencies of ABO blood groups as well as their distributions in different regions of Morocco. However, there are no detailed published data concerning ABO genetic polymorphism up to date. Regarding the ABO system importance in transfusion medicine and anthropology. Our aim is to determine the ABO phenotypic and genetic polymorphism within Moroccan blood donors. Subjects and Methods: The ABO phenotype was determined using Olympus PK 7300 Automate and two lots of reagents. Genotyping of 120 subjects taken randomly and of 60 subjects with AB blood groups was performed by allele‐specific polymerase chain reaction (AS‐PCR) technique. The direct sequencing concerned five DNA of individuals whose genotypes were undetermined by AS‐PCR. Results: The ABO allelic frequencies found among 9271 blood donors are 0·681, 0·205 and 0·114 for O, A and B alleles respectively. A total of 10 alleles and 20 genotypes have been revealed in 120 blood donors. The ABO genetic frequencies of which are 0·346, 0·233, 0·121, 0·113, 0·058, 0·021, 0·0125, 0·0042, 0·0042 and 0·0042 for ABO*O02, ABO*O01, ABO*B101, ABO*A101, ABO*A201, ABO*A102, ABO*O03, ABO*O306, ABO*O107 and ABO*Onv alleles respectively. Furthermore, our results suggested the existence of A2 allele depression by B allele among 16·18% of AB subjects. This depression concerns 96·66% among A201 /B101 and 3·34% among A206 /B101 subjects. Conclusion: This study is the first in Morocco concerning the ABO genetic polymorphism. The direct sequencing of ABO gene taking into account a large population lets us precise the genetic diversity and consolidate the hypothesis of the existence of the A2 allele depression by B allele within the Moroccan population.